Ocular Vestibular Evoked Myogenic Potentials - Felipe, Lilian (Int Arch Otorhinolaryngol, 2013)
Introduction Diagnostic testing of the vestibular system is an essential component of treating patients with balance dysfunction. Until recently, testing methods primarily evaluated the integrity of the horizontal semicircular canal, which is only a portion of the vestibular system. Recent advances in technology have afforded clinicians the ability to assess otolith function through vestibular evoked myogenic potential (VEMP) testing. VEMP testing from the inferior extraocular muscles of the eye has been the subject of interest of recent research. Objective To summarize recent developments in ocular VEMP testing. Results Recent studies suggest that the ocular VEMP is produced by otolith afferents in the superior division of the vestibular nerve. The ocular VEMP is a short latency potential, composed of extraocular myogenic responses activated by sound stimulation and registered by surface electromyography via ipsilateral otolithic and contralateral extraocular muscle activation. The inferior oblique muscle is the most superficial of the six extraocular muscles responsible for eye movement. Therefore, measurement of ocular VEMPs can be performed easily by using surface electrodes on the skin below the eyes contralateral to the stimulated side. Conclusion This new variation of the VEMP procedure may supplement conventional testing in difficult to test populations. It may also be possible to use this technique to evaluate previously inaccessible information on the vestibular system.